2005
DOI: 10.1080/09273940590951115
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin-Associated Panuveitis with Retinal Vasculitis in Pulmonary Tuberculosis

Abstract: Four cases of rifabutin-associated panuveitis with retinal vasculitis are reported in patients with active pulmonary tuberculosis. Immunogenicity of Mycobacterium tuberculosis as well as the very low weight of the patients might be implicated in the development of this unusual form of rifabutin-associated uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Although mild to moderate vitritis frequently develops in rifabutin-associated uveitis, posterior involvement is less frequent [5–7]. Similar to the previous cases, our patient presented with uveitis several months after the start of rifabutin and responded quickly to topical corticosteroids and discontinuation of rifabutin.…”
Section: Discussionsupporting
confidence: 81%
“…Although mild to moderate vitritis frequently develops in rifabutin-associated uveitis, posterior involvement is less frequent [5–7]. Similar to the previous cases, our patient presented with uveitis several months after the start of rifabutin and responded quickly to topical corticosteroids and discontinuation of rifabutin.…”
Section: Discussionsupporting
confidence: 81%
“…The dose required to cause uveitis could range anywhere from 300mg to 1800mg as established by Skolik et al [13], The higher the dose and duration of treatment, the greater is the risk of associated uveitis [14]. Our patient developed uveitis within one month of initiation of therapy at a standard dose of 300mg, the early onset of the drug side effect is attributable to the inhibition of its metabolism by ritonavir.…”
Section: Discussionmentioning
confidence: 62%
“…The dose range of rifabutin associated with uveitis goes between 300 and 1800 mg daily [5,9]. Shafran and colleagues demonstrated that patients on 300 mg/day of rifabutin rarely developed uveitis, and when it occurred, it took at least 7 months of medication use for the uveitis to develop [3].…”
Section: Discussionmentioning
confidence: 99%
“…There is only one reported case in the literature of an HIV+ cachectic patient with 150 mg/day of rifabutin combined with triple therapy for HIV causing panuveitis and retinal vasculitis after 6 months of treatment [5]. Low body weight is another known risk factor for the development of rifabutin-induced uveitis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation